vox homeobox gene: a novel regulator of midbrain-hindbrain boundary development in medaka fish? - Fabian, Peter; Pantzartzi, Chrysoula N; Kozmikova, Iryna; Kozmik, Zbynek (Development genes and evolution, 2016)
The midbrain-hindbrain boundary (MHB) is one of the key organizing centers of the vertebrate central nervous system (CNS). Its patterning is governed by a well-described gene regulatory network (GRN) involving several transcription factors, namely, pax, gbx, en, and otx, together with signaling molecules of the Wnt and Fgf families. Here, we describe the onset of these markers in Oryzias latipes (medaka) early brain development in comparison to previously known zebrafish expression patterns. Moreover, we show for the first time that vox, a member of the vent gene family, is expressed in the developing neural tube similarly to CNS markers. Overexpression of vox leads to profound changes in the gene expression patterns of individual components of MHB-specific GRN, most notably of fgf8, a crucial organizer molecule of MHB. Our data suggest that genes from the vent family, in addition to their crucial role in body axis formation, may play a role in regionalization of vertebrate CNS.
Keywords: Mesencephalon; Embryo, Nonmammalian; rybí proteiny; Rhombencephalon; Midbrain-hindbrain boundary; Gene Regulatory Networks; Heat shock element; Fish Proteins; Gene regulatory network; mezencefalon; medaka; genové regulační sítě; Animals; Oryzias; vox; zvířata; fgf8; rombencefalon; Homeodomain Proteins; homeodoménové proteiny; embryo nesavčí